Net-phytoplankton communities and influencing factors in the Antarctic Peninsula region in the late austral summer 2019/2020 - Liu, Lu; Zhang, Jichang; Zhao, Yunxia; Luan, Qingshan; Zhao, Xianyong; Wang, Xinliang (Frontiers in Marine Science, 2023)
The waters near the Antarctic Peninsula are characterized with unique oceanographic conditions and rich krill resources. Based on samples collected around the South Shetland Islands (SSI) in austral summer of 2019/2020, the net- phytoplankton community structure and relevant major biotic and abiotic influencing factors were investigated. Eighty-one taxa were identified by light microscope, and diatoms were the most abundant group. The most abundant species were Chaetoceros atlanticus, C. criophilus, C. dichaeta, Fragilariopsis kerguelensis and Pseudo−nitzschia lineola. The abundance and Shannon-Weaver index of net-phytoplankton ranged from 100 to 2.64×107 cells/m3 and 0.0747 to 4.0176 respectively, with significantly low values detected in the Bransfield Strait (BS) and high values in the west of the SSI. The dissimilarity was mainly caused by the differences in abundance of diatoms (including Thalassiothrix antarctica and the species in genus Rhizosolenia, Chaetoceros, Fragilariophsis). These diatoms and Dictyocha speculum were found in higher abundance in the west of the SSI, while Corethron pennatum and cryptophytes were found in higher abundance in the BS. Combined with acoustic density of krill and environmental data (Sea Surface Temperature and Sea Ice Concentration). The multivariate analysis suggested that phytoplankton community was positively affected by the SST, and the acoustic- derived krill density would be associated with the spatial distribution of pennate diatoms. This study enhances the knowledge about the selective feeding for krill and provides ecological implications for the Antarctic marine ecosystem.